Listening Strategies Applied by Female and Male Students at SMP Negeri 1 Sungguminasa - Mila Dwirezky Anggraeni; A. Muliati; Syarifah Faradiba (Journal of Excellence in English Language Education, 2023)
This study’s goal was to identify the variations in listening strategies utilized by female and male students during the learning process. This research was conducted at SMP Negeri 1 Sungguminasa. To achieve the research objectives, this research was conducted using a comparative descriptive technique using a qualitative strategy. Students from SMP Negeri 1 Sungguminasa's class IX A made up the study population. The instruments employed in this study were questionnaire and interview. The collected research data were analyzed to describe the percentage, frequency and students’ statements in listening strategies. According to the findings, there are disparities in the listening strategies used by male and female students. The study findings revealed that 63% of female students used metacognitive, 68% cognitive, and 69% socio-affective strategies when listening, compared to 59% of male students who used metacognitive, 61% cognitive, and 37% socio-affective strategies.